Effect of Accompaniment Trained Peer Neighbor on Exclusive Breastfeeding Duration and Prevalence: A Quasi-Experimental Study - Irmawati, Irmawati; Nugraheni, Sri Achadi; Sulistiyani, Sulistiyani; Sriatmi, Ayun (Jurnal Kesehatan Masyarakat, 2024)
Introduction: Postpartum care in the hospital was very short, while the breastfeeding period was very long. On returning home, mother need the closest, affordable and ongoing supporting of trained neighbors for exclusive breastfeeding up to 6 months. This study aimed to examine the effect of accompaniment by trained peer neighbor (ATPN) on exclusive breastfeeding (EBF) duration and prevalence. Methods: The experimental quasi-design was used to compare duration of EBF in the intervention group (n=49) and the control group (n=49). The intervention group received ATPN by scheduled home visits 15 times with providing informational and practical support. The control group received the postpartum care-standard. Duration of EBF was measured weekly to 24th week postpartum. Survival analysis was used to compare duration of EBF between groups. A Cox proportional hazards regression analysis was used to estimate adjusted hazard ratios for cessation of EBF. Results: The intervention increases the duration of EBF. Median duration of EBF in the intervention and control group were 21.63 weeks and 15.85 weeks respectively (p0.001).  The prevalence of EBF at 12, 20, 24 weeks for the intervention versus control groups were (93.8% vs 69.3 %) (79.5% vs 44.8%), (59.1% vs 12.2%) respectively. Mothers in the control group were four times more likely to cessation EBF each of time than were mothers in the intervention group (HR 4.24; 95% CI: 2.56, 6.99). Conclusion: The ATPN effectively increases exclusive breastfeeding duration. It was easy to implement at a lower cost, sustainable, and effective.